Parental experiences of a diagnosis of neonatal diabetes and perceptions of newborn screening for glucose: a qualitative study. Issue 11 (4th November 2020) - Shepherd, Maggie; Knight, Bridget A; Laskey, Katherine; McDonald, Timothy James
Abstract : Neonatal diabetes presents <6 months of life but delays in recognition result in presentation with life-threatening hyperglycaemia/diabetic ketoacidosis. Early identification and rapid genetic diagnosis is crucial and ensures correct treatment/management. Adding 'glucose' to newborn bloodspot screening (NBS) could aid prompt detection but requires evidence of parental acceptance. Objectives: Increase understanding of parental experience of presentation/recognition of neonatal diabetes and perceptions of glucose testing within NBS. Setting: UK families confirmed with a genetic diagnosis of neonatal diabetes, November 2014–2018, were invited to participate. Participants: In-depth qualitative interviews were conducted with 10 parents of 14 children. 8 had transient neonatal diabetes: KCNJ11 (n=5), ABCC8 (n=1), 6q24 (n=2), 6 had permanent neonatal diabetes: KCNJ11 (n=4), INS (n=1), homozygous GCK (n=1). Primary and secondary outcome measures: Interviews audio recorded, transcribed and subjected to thematic content analysis. Results: 3 key themes emerged: Babies were extremely ill at hospital admission, with extended stays in intensive care required. Identification of diabetes was not 'standardised' and perceived a 'chance' finding. Adding glucose to NBS was universally considered extremely positive. Conclusions: Diagnosis of neonatal diabetes is frequently delayed, resulting in critically ill presentation with prolonged intensive care support, additional healthcare costs and familial distress. Potential to detect hyperglycaemia earlier was universally endorsed by parents with no negative consequences identified. Although further study including a larger number of individuals is needed to confirm our findings this study provides the first evidence of acceptability of glucose testing fulfilling Wilson-Jungner criteria for implementation within the NBS programme.